Manufacturing method of rare earth magnet

The manufacturing method for R-FE-B-based rare earth magnets uses a specific precursor composition and LA-modified material to maintain squareness and residual magnetization by preventing the formation of tetragonal RT phases, improving magnetic performance at high temperatures.

JP7622574B2Active Publication Date: 2025-01-28TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021120915
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-21
Publication Date
2025-01-28
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

Existing methods of producing R-FE-B-based rare earth magnets that replace part of FE with CO to enhance high-temperature magnetic characteristics result in a decrease in squareness, as measured by the HR/HC ratio, and residual magnetization.

Method used

A manufacturing method involving a rare earth magnet precursor with specific molar ratios and a modified material containing LA, which is spread inside the precursor to suppress the formation of RT phases with a tetragonal crystal structure, maintaining the squareness and residual magnetization.

Benefits of technology

The method effectively suppresses the decrease in squareness and residual magnetization of R-FE-B-based rare earth magnets by eliminating RT phases with tetragonal crystal structures, thereby enhancing magnetic characteristics at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622574000003
    Figure 0007622574000003
  • Figure 0007622574000004
    Figure 0007622574000004
  • Figure 0007622574000005
    Figure 0007622574000005
Patent Text Reader

Abstract

To provide a manufacturing method of a rare earth magnet, capable of suppressing the deterioration of rectangularity even if part of Fe is substituted with Co.SOLUTION: A manufacturing method of a rare earth magnet of the present disclosure includes: preparing a rare earth magnet precursor including a main phase having a crystal structure of an R2T14 B type (where, R represents a rare earth element, and T represents a transition metal element.) and a grain boundary phase existing around the main phase; and diffusing and permeating a modifier containing a rare earth element, within the rare earth magnet precursor. The rare earth magnet precursor contains Co, and the molar ratio x of La to all rare earth elements in the modifier satisfies an expression of 0.09<x<0.19.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing rare earth magnets. 14 The present invention relates to a method for producing a rare earth magnet having a main phase with a B-type (where R is a rare earth element and T is a transition metal element) crystal structure. [Background technology]

[0002] The R-Fe-B rare earth magnet comprises a main phase and a grain boundary phase surrounding the main phase. 14 This is a magnetic phase with a B-type crystal structure. This main phase allows for high remanent magnetization. For this reason, R-Fe-B rare earth magnets are often used in motors.

[0003] When permanent magnets, including R-Fe-B rare earth magnets, are used in motors, the permanent magnets are placed in an external magnetic field environment that changes periodically. As a result, the permanent magnets can be demagnetized by an increase in the external magnetic field. When using permanent magnets in motors, they are required to be as little demagnetized as possible when the external magnetic field increases. A demagnetization curve indicates the degree of demagnetization in response to an increase in the external magnetic field, and a demagnetization curve that meets the above requirements has a rectangular shape. For this reason, satisfaction of the above requirements is said to have excellent rectangular shape.

[0004] Since motors generate heat during operation, the permanent magnets used in motors are required to have high magnetic properties at high temperatures. In this specification, unless otherwise specified, high temperature means a temperature range of 130 to 200°C, particularly 140 to 180°C.

[0005] In order to improve the magnetic properties of R-Fe-B rare earth magnets at high temperatures, it is useful to increase the Curie temperature by substituting part of Fe with Co. For example, Non-Patent Document 1 discloses that in an R-Fe-B rare earth magnet in which Nd is selected as R, the Curie temperature can be increased by substituting part of Fe with Co. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Kazuhiko Mashima et al., "Effect of Co Addition on Sintering Characteristics of Nd2Fe14B Magnet Alloy," Powder and Powder Metallurgy, Vol. 39, No. 10, pp. 855-859, 1992. Summary of the Invention [Problem to be solved by the invention]

[0007] When a part of Fe is simply replaced with Co, as in the R-Fe-B rare earth magnet disclosed in Non-Patent Document 1, the Curie temperature rises and the remanence at high temperatures improves, but the squareness decreases. For this reason, the inventors have found a problem that an R-Fe-B rare earth magnet in which the decrease in squareness is suppressed even when a part of Fe is replaced with Co is desired. Since the squareness at room temperature and the squareness at high temperatures are highly correlated, in this specification, unless otherwise specified, the "squareness" means the squareness at room temperature. In addition, the squareness is evaluated by the squareness ratio expressed as Hr / Hc. Hc is the coercive force, and Hr is the magnetic field at 5% demagnetization. The magnetic field at 5% demagnetization means the magnetic field in the second quadrant (demagnetization curve) of the hysteresis curve when the magnetization is 5% lower than the remanence (magnetic field when the applied magnetic field is 0 kA / m).

[0008] The present disclosure has been made to solve the above problems, and aims to provide a method for producing a rare earth magnet that can suppress a decrease in squareness even when a portion of Fe is substituted with Co. [Means for solving the problem]

[0009] The present inventors have conducted intensive research to achieve the above object, and have completed the method for producing a rare earth magnet according to the present disclosure. The method for producing a rare earth magnet according to the present disclosure includes the following aspects. 1. R2T 14Prepare a rare earth magnet precursor comprising a main phase having a B-type crystal structure (wherein R is a rare earth element and T is a transition metal element), and a grain boundary phase existing around the main phase, and Diffuse and infiltrate a modifier containing a rare earth element into the interior of the rare earth magnet precursor, including the rare earth magnet precursor contains Co, and the molar ratio x of La to the total rare earth elements in the modifier satisfies 0.09 < x < 0.19, A method for manufacturing a rare earth magnet. <2> The method according to item <1>, wherein the average particle size of the main phase is 1 to 10 μm. <3> The overall composition of the rare earth magnet precursor in terms of molar ratio is represented by the formula R 1 y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v (wherein R 1 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho, M 1 is one or more elements selected from the group consisting of Ga, Al, Cu, Au, Ag, Zn, In, and Mn and inevitable impurity elements, and 12.0 ≤ y ≤ 20.0, 0.10 ≤ z ≤ 0.30, 5.0 ≤ w ≤ 20.0, and 0 ≤ v ≤ 2.0 ) The method according to item <1> or <2>. <4> The method according to item <3>, wherein R 1 is one or more elements selected from the group consisting of Nd and Pr. <5> The composition of the modifier is represented by the formula (R 2 (1-x) La x ) (1-s) M 2 s (wherein R 2 is one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho, M2 is a metal element other than the rare earth element alloyed with R 2 and inevitable impurity elements, and 0.09 < x < 0.19 and 0.05 ≦ s ≦ 0.40. The method according to any one of <1> to <3> represented by <6> The above-mentioned R 2 is one or more elements selected from the group consisting of Nd and Tb, and the method according to <5>. <7> The above-mentioned M 2 is Cu and inevitable impurity elements, and the method according to <5> or <6>.

Advantages of the Invention

[0010] According to the method for producing a rare earth magnet of the present disclosure, by diffusing and infiltrating a modifier containing a predetermined ratio of La into the inside of a rare earth magnet precursor in which a part of Fe is replaced by Co, the ferromagnetic phase containing Co in the grain boundary phase can be demagnetized. As a result, a decrease in the squareness of the obtained R-T-B-based rare earth magnet can be suppressed. That is, according to the present disclosure, even if a part of Fe is replaced by Co, it is possible to provide a method for producing an R-T-B-based rare earth magnet capable of suppressing a decrease in squareness.

Brief Description of the Drawings

[0011] [Figure 1A] FIG. 1A is an explanatory diagram schematically showing the structure of a rare earth magnet precursor used in the production method of the present disclosure. [Figure 1B] FIG. 1B is an enlarged explanatory diagram of the portion indicated by the broken line in FIG. 1A. [Figure 2A] FIG. 2A is an explanatory diagram schematically showing the structure of a rare earth magnet obtained by the production method of the present disclosure. [Figure 2B] FIG. 2B is an enlarged explanatory diagram of the portion indicated by the broken line in FIG. 2A. [Figure 3A] FIG. 3A is an explanatory diagram schematically showing the structure of a rare earth magnet after diffusing and infiltrating a modifier with an insufficient La content. [Figure 3B] FIG. 3B is an enlarged explanatory diagram of the portion indicated by the broken line in FIG. 3A. [Figure 4A] FIG. 4A is an explanatory diagram that shows a schematic diagram of the structure of a rare earth magnet after diffusion infiltration of a modifier containing an excessive La content. [Figure 4B] FIG. 4B is an explanatory diagram showing an enlarged portion of FIG. 4A enclosed by a dashed line. [Diagram 5] FIG. 5 is an explanatory diagram that illustrates a schematic diagram of a cooling device used in the strip casting method. [Figure 6] FIG. 6 is a graph showing the relationship between the molar ratio x of La to the total rare earth elements in the modifier and the squareness ratio (Hr / Hc) for each sample. [Figure 7] FIG. 7 is a graph showing the demagnetization curves of each sample. [Figure 8] FIG. 8 is an explanatory diagram showing an SEM image and the results of area analysis of the sample of Example 1. [Figure 9] FIG. 9 is an explanatory diagram showing an SEM image and the results of area analysis of the sample of Comparative Example 1. [Figure 10] FIG. 10 is an explanatory diagram showing an SEM image and the results of area analysis of the sample of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the manufacturing method for a rare earth magnet according to the present disclosure (hereinafter referred to as the "manufacturing method according to the present disclosure") will be described in detail. Note that the manufacturing method according to the present disclosure is not limited to the embodiment described below.

[0013] Without being bound by theory, findings regarding the reason why the manufacturing method of the present disclosure can obtain an RTB rare earth magnet in which the decrease in squareness is suppressed will be described with reference to the drawings. FIG. 1A is an explanatory diagram showing a typical structure of a rare earth magnet precursor used in the manufacturing method of the present disclosure. FIG. 1B is an explanatory diagram showing an enlarged view of the portion indicated by the dashed line in FIG. 1A. FIG. 2A is an explanatory diagram showing a typical structure of a rare earth magnet obtained by the manufacturing method of the present disclosure. FIG. 2B is an explanatory diagram showing an enlarged view of the portion indicated by the dashed line in FIG. 2A. FIG. 3A is an explanatory diagram showing a typical structure of a rare earth magnet after diffusion infiltration of a modifier having an insufficient La content. FIG. 3B is an explanatory diagram showing an enlarged view of the portion indicated by the dashed line in FIG. 3A. FIG. 4A is an explanatory diagram showing a typical structure of a rare earth magnet after diffusion infiltration of a modifier having an excessive La content. FIG. 4B is an explanatory diagram showing an enlarged view of the portion indicated by the dashed line in FIG. 4A.

[0014] 1A and 1B, a rare earth magnet precursor 50 used in the manufacturing method of the present disclosure comprises a main phase 10 and a grain boundary phase 20 present around the main phase 10. The grain boundary phase 20 has an adjacent portion 22 where two main phases 10 are adjacent to each other, and a triple point 24 surrounded by three main phases 10.

[0015] Main phase 10 is R2T 14 The phase 26 has a B-type crystal structure. The grain boundary phase 20 contains various phases having a crystal structure richer in R than the main phase 10. Among the phases of the grain boundary phase 20, the phase having the RT2-type crystal structure exhibits ferromagnetic behavior. When a part of the Fe in the rare earth magnet precursor 50 is replaced with Co, the phase 26 having the RT2-type crystal structure is likely to exist in the grain boundary phase 20, particularly in the adjacent portion 22. Such a phase 26 having the RT2-type crystal structure inhibits magnetic separation between the main phases 10, reduces the coercive force, and leads to a decrease in squareness.

[0016] When a certain proportion of La is present in the grain boundary phase 20 of the rare earth magnet precursor 50, the phase 26 having the RT2 type crystal structure can be reduced.

[0017] Therefore, a modifier containing a predetermined ratio of La is diffused and infiltrated into the inside of a rare earth magnet precursor 50 as shown in Figs. 1A and 1B. The modifier mainly diffuses and infiltrates into the grain boundary phase 20 of the rare earth magnet precursor 50. Therefore, as shown in Figs. 2A and 2B, in the rare earth magnet 100 after the modifier is diffused and infiltrated, the phase 26 having the RT2 type crystal structure that existed in the adjacent portion 22 of the rare earth magnet precursor 50 of Figs. 1A and 1B is almost eliminated. It is considered that a phase that is even more R-rich than the phase 26 having the RT2 type crystal structure is formed in the adjacent portion 22. It is also considered that a phase that is even more R-rich than the phase 26 having the RT2 type crystal structure is formed in the triple point 24. These phases that are more R-rich than the phase 26 having the RT2 type crystal structure contribute to magnetically separating the main phases 10 from each other, thereby suppressing a decrease in coercivity and suppressing a decrease in squareness.

[0018] In contrast, when a modifier with an insufficient La content is diffused and infiltrated into the rare earth magnet precursor 50 as shown in FIGS. 1A and 1B, the phase 26 having the RT2 type crystal structure present in the adjacent portion 22 cannot be sufficiently eliminated. Therefore, as shown in FIGS. 3A and 3B, many phases 26 having the RT2 type crystal structure remain in the adjacent portion 22 of the rare earth magnet 100 after the modifier is diffused and infiltrated. As a result, the decrease in coercivity cannot be suppressed, and the decrease in squareness cannot be suppressed. It is considered that the diffusion and infiltration of the modifier forms a phase richer in R than before the diffusion and infiltration of the modifier at the triple point 24, but this does not suppress the decrease in coercivity and squareness.

[0019] Furthermore, when a modifier containing an excessive amount of La is diffused and infiltrated into the rare earth magnet precursor 50 as shown in FIG. 1A and FIG. 1B, a phase 26 having an RT2 type crystal structure is reformed, particularly at the triple point 24, as shown in FIG. 4A and FIG. 4B. In order to eliminate the phase 26 having an RT2 type crystal structure by the diffusion and infiltration of the modifier, the grain boundary phase 22 must dissolve the single Fe generated by the elimination. However, when the solid solution becomes saturated, the phase 26 having an RT2 type crystal structure is reformed. Then, the reformed phase 26 having an RT2 type crystal structure reduces the coercive force and the squareness. In addition, the excess La is present in the adjacent portion 22 as a La phase 28.

[0020] For this reason, by diffusing and infiltrating a modifier containing a prescribed proportion of La into the interior of rare earth magnet precursor 50, it is possible to obtain an RTB rare earth magnet in which the decrease in squareness is suppressed.

[0021] To suppress the formation of phase 26 having an RT2 type crystal structure, it is sufficient that rare earth magnet precursor 50 contains a predetermined ratio of La, without diffusing and infiltrating the modifier as described above. Such rare earth magnet precursor 50 is obtained by cooling a molten metal containing a predetermined ratio of La, and at that time, main phase 10 also contains La. When main phase 10 contains a light rare earth element, the remanence decreases. Because La is a light rare earth element, such rare earth magnet precursor 50 has low remanence.

[0022] In contrast, in the manufacturing method of the present disclosure, La is supplied to the grain boundary phase 20 by diffusion and penetration of a modifier. Therefore, the rare earth magnet precursor 50 used in the manufacturing method of the present disclosure does not need to contain La. For this reason, the manufacturing method of the present disclosure is advantageous in that it is possible to suppress a decrease in coercivity and a decrease in squareness without decreasing remanent magnetization.

[0023] Based on the findings described above, the constituent elements of the manufacturing method of the present disclosure will be described below.

[0024] 《Manufacturing method》 The manufacturing method of the present disclosure includes a rare earth magnet precursor preparation step, a modifier diffusion and infiltration step, and optionally a heat treatment step. Each step will be described below.

[0025] <Rare earth magnet precursor preparation process> First, a rare earth magnet precursor is prepared. As shown in Fig. 1, a rare earth magnet precursor 50 used in the manufacturing method of the present disclosure includes a main phase 10 and a grain boundary phase 20. The grain boundary phase 20 is present around the main phase 10.

[0026] The main phase is R2T 14 It has a B-type crystal structure. R is a rare earth element, and T is a transition metal element. In this specification, unless otherwise specified, the rare earth elements are 17 elements, namely Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Of these, Sc, Y, La, and Ce are light rare earth elements, unless otherwise specified. Furthermore, Pr, Nd, Pm, Sm, and Eu are medium rare earth elements, unless otherwise specified. And, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu are heavy rare earth elements, unless otherwise specified. In general, the rarity of heavy rare earth elements is high, and the rarity of light rare earth elements is low. The rarity of medium rare earth elements is between that of heavy rare earth elements and light rare earth elements. Note that Sc is scandium, Y is yttrium, La is lanthanum, Ce is cerium, Pr is praseodymium, Nd is neodymium, Pm is promethium, Sm is samarium, Eu is europium, Gd is gadolinium, Tb is terbium, Dy is dysprosium, Ho is holmium, Er is erbium, Tm is thulium, Yb is ytterbium, and Lu is ruthenium.

[0027] The rare earth magnet precursor is obtained by cooling a molten metal having the composition. The manufacturing method of the rare earth magnet precursor 50 will be described in detail later. The particle size of the main phase 10 in the rare earth magnet precursor 50 depends on the cooling rate of the molten metal. If the cooling rate of the molten metal is slow, many phases having an RT2 type crystal structure are formed in the grain boundary phase 20. Therefore, when using the rare earth magnet precursor 50 obtained at such a cooling rate, the manufacturing method of the present disclosure is particularly useful. The average particle size of the main phase in the rare earth magnet precursor 50 obtained at such a cooling rate may be 1.0 μm or more, 3.0 μm or more, 5.0 μm or more, or 6.0 μm or more, and may be 10.0 μm or less, 8.0 μm or less, 6.0 μm or less, or 6.5 μm or less.

[0028] The average grain size of the main phase is measured as follows. A certain region is defined in a scanning electron microscope image or a transmission electron microscope image observed perpendicular to the easy axis of magnetization, and multiple lines are drawn perpendicular to the easy axis of magnetization for the main phase present in this certain region, and the diameter (length) of the main phase is calculated from the distance between the intersecting points within the main phase particle (cutting method). If the cross section of the main phase is close to a circle, it is converted to the diameter equivalent to the circle of the projected area. If the cross section of the main phase is close to a rectangle, it is converted to a rectangular approximation. The D of the diameter (length) distribution (particle size distribution) obtained in this way is 50 The value is the average particle size.

[0029] The rare earth magnet precursor contains Co. This can increase the Curie temperature of the rare earth magnet obtained by the manufacturing method of the present disclosure, and as a result, can improve the magnetic properties at high temperatures. The main element of the rare earth magnet precursor is typically Fe, and a part of Fe is substituted with Co. The ratio of Co to Fe, in terms of molar ratio, can be, for example, 0.10 or more, 0.12 or more, 0.14 or more, or 0.16 or more, and can be 0.30 or less, 0.28 or less, 0.26 or less, 0.24 or less, 0.22 or less, or 0.20 or less. Co is cobalt, and Fe is iron.

[0030] R2T 14From the viewpoint of facilitating the formation of a B-type crystal structure and facilitating the formation of a high residual magnetization, the rare earth element in the rare earth magnet precursor is preferably one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho. Typically, a portion of the rare earth element in the rare earth magnet precursor 50 may be substituted with an inexpensive light rare earth element. When a light rare earth element is contained, the residual magnetization decreases, so the content ratio (substitution ratio) of the light rare earth element may be appropriately determined in consideration of the desired residual magnetization.

[0031] The overall composition of the rare earth magnet precursor as explained above can be expressed by the following formula, for example: Note that the overall composition of the rare earth magnet precursor means the combined composition of all of the main phases and grain boundary phases in the rare earth magnet precursor.

[0032] The composition of the rare earth magnet precursor is, for example, expressed by the molar ratio as follows: 1 y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v In this formula, R 1 is y moles, the sum of Fe and Co is (100-ywv) moles, B is w moles, and M 1 This means that there are v moles of Fe. (1-z) Co z means that, based on the molar ratio of the total of Fe and Co, (1-z) Fe is present and z Co is present.

[0033] In the above formula, R 1 may be one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho. In the above formula, Fe is iron, Co is cobalt, and B is boron. Also, M 1 may be one or more elements selected from the group consisting of Ga, Al, Cu, Au, Ag, Zn, In, and Mn, as well as unavoidable impurity elements, where Ga is gallium, Al is aluminum, Cu is copper, Au is gold, Ag is silver, Zn is zinc, In is indium, and Mn is manganese.

[0034] The constituent elements of the rare earth magnet precursor represented by the above formula will now be described.

[0035] ·R 1 R 1 is an essential component for the rare earth magnet obtained by the manufacturing method of the present disclosure. 1 R is preferably one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho. 1 is the main phase (R2T 14 From the viewpoint of the balance between remanence and coercivity and price, R 1 R is preferably one or more elements selected from the group consisting of Nd and Pr. 1 When Nd and Pr are used together, didymium may be used.

[0036] ·R 1 Content ratio of In the above formula, R 1 The content ratio of is represented by y and satisfies 12.0≦y≦20.0. The value of y is the content ratio relative to the entire rare earth magnet precursor, and corresponds to mol % (atomic %).

[0037] If y is 12.0 or more, the rare earth magnet precursor does not contain a large amount of αFe phase, and a sufficient amount of the main phase (R 14 A phase having a B-type crystal structure can be obtained. From this viewpoint, y may be 12.5 or more, 13.0 or more, or 13.5 or more. On the other hand, if y is 20.0 or less, the grain boundary phase does not become excessive. From this viewpoint, y may be 19.0 or less, 18.0 or less, 17.0 or less, 16.0 or less, 15.0 or less, 14.0 or less, or 13.9 or less.

[0038] ·B B is the main phase (R2T 14 B-type crystal structure) and affects the abundance ratio of the main phase and grain boundary phase.

[0039] The content ratio of B is represented by w in the above formula. The value of w is the content ratio relative to the entire rare earth magnet precursor, and corresponds to mole % (atomic %). If w is 20.0 or less, it is possible to obtain a rare earth magnet precursor in which the main phase and grain boundary phase are appropriately present. From this viewpoint, w may be 18.0 or less, 16.0 or less, 14.0 or less, 12.0 or less, 10.0 or less, 8.0 or less, 6.0 or less, or 5.8 or less. On the other hand, if w is 5.0 or more, Th2Zn 17 Type and / or Th2Ni 17 It is difficult for a large amount of phases with the R2T type crystal structure to occur. 14 The formation of a phase having a crystal structure of type B is less inhibited. From this viewpoint, w may be 5.2 or more, 5.4 or more, 5.5 or more, or 5.7 or more.

[0040] M 1 M 1 is an element that can be contained within a range that does not impair the properties of the rare earth magnet obtained by the manufacturing method of the present disclosure. 1 may contain unavoidable impurity elements. In this specification, unavoidable impurity elements refer to impurity elements contained in raw materials or impurity elements mixed in during the manufacturing process, etc., which cannot be avoided, or which would result in a significant increase in manufacturing costs if avoided. Impurity elements mixed in during the manufacturing process include elements that are included for manufacturing reasons to the extent that they do not affect the magnetic properties. Additionally, unavoidable impurity elements include R 1 and R 2 The rare earth elements selected as R are not included, but include rare earth elements that are inevitably mixed in due to the reasons described above. 2 More on this later.

[0041] The element M may be contained in an amount that does not impair the properties of the rare earth magnet obtained by the manufacturing method of the present disclosure. 1 Examples of the element include one or more elements selected from the group consisting of Ga, Al, Cu, Au, Ag, Zn, In, and Mn.1 As long as they are present at or below the upper limit of the content, these elements do not substantially affect the magnetic properties. Therefore, these elements may be treated as unavoidable impurity elements. 1 As a result, it may contain unavoidable impurity elements. 1 As the impurity element, at least one element selected from the group consisting of Ga, Al, and Cu, and unavoidable impurity elements are preferable.

[0042] In the above formula, M 1 The content ratio of is represented by v. The value of v is the content ratio relative to the entire rare earth magnet precursor, and corresponds to mole % (atomic %). If the value of v is 2.0 or less, the magnetic properties of the rare earth magnet obtained by the manufacturing method of the present disclosure are not impaired. From this viewpoint, v may be 1.5 or less, 1.0 or less, 0.65 or less, 0.6 or less, or 0.5 or less. M 1 Since it is impossible to completely eliminate Ga, Al, Cu, Au, Ag, Zn, In, and Mn as well as unavoidable impurity elements, there is no practical problem even if the lower limit of v is 0.05, 0.1, or 0.2.

[0043] Fe Fe is the main phase (R2T 14 It is the main component that constitutes the B-type crystal structure phase and the grain boundary phase. A part of Fe is replaced by Co.

[0044] ·Co Co is an element that substitutes for part of Fe in the main phase and grain boundary phase, which increases the Curie point of the rare earth magnet obtained by the manufacturing method of the present disclosure and improves the magnetic properties at high temperatures, in particular the remanence magnetization at high temperatures.

[0045] Fe:Co molar ratio In the above formula, the molar ratio of Fe to Co is (1-z):z. If z is 0.1 or more, the magnetic properties at high temperatures, particularly the residual magnetization at high temperatures, are significantly improved due to the rise in the Curie point. From this viewpoint, z may be 0.12 or more, 0.14 or more, or 0.16 or more. On the other hand, if z is 0.30 or less, the phase having the RT2 type crystal structure can be effectively eliminated by diffusing and infiltrating a modifier containing a predetermined ratio of La. From this viewpoint, z may be 0.28 or less, 0.26 or less, 0.24 or less, 0.22 or less, or 0.20 or less. In addition, since Co is expensive, it is advantageous to be in the above range.

[0046] Total content of Fe and Co The total content of Fe and Co is R 1 , B, and M 1 and is expressed as (100-ywv). As described above, the values ​​of y, w, and v are the content ratios relative to the entire rare earth magnet precursor, so (100-ywv) corresponds to mole % (atomic %). When y, w, and v are within the ranges described above, the main phase 10 and grain boundary phase 20 as shown in FIG. 1A are obtained.

[0047] ·Method of manufacturing rare earth magnet precursor The method for producing the rare earth magnet precursor can be a known method for producing an RTB rare earth magnet, which will be outlined below.

[0048] The molten metal having the composition of the rare earth magnet precursor is cooled. Examples of the method for cooling the molten metal include a method using a book mold and a strip casting method. The strip casting method is preferable from the viewpoint of obtaining a stable cooling rate and being able to continuously cool a large amount of molten metal. Here, the strip casting method will be explained with reference to the drawings. FIG. 5 is an explanatory diagram that shows a schematic diagram of a cooling device used in the strip casting method.

[0049] The cooling device 70 includes a melting furnace 71, a tundish 73, and a cooling roll 74. Raw materials are melted in the melting furnace 71 to prepare a molten metal 72 having the above-mentioned composition. The molten metal 72 is supplied to the tundish 73 at a constant supply rate. The molten metal 72 supplied to the tundish 73 is supplied to the cooling roll 74 from an end of the tundish 73 by its own weight.

[0050] The tundish 73 is made of ceramics or the like, and can temporarily store the molten metal 72 that is continuously supplied from the melting furnace 71 at a predetermined flow rate, and can straighten the flow of the molten metal 72 to the chill roll 74. The tundish 73 also has a function of adjusting the temperature of the molten metal 72 immediately before it reaches the chill roll 74.

[0051] The chill roll 74 is made of a material having high thermal conductivity such as copper or chromium, and the surface of the chill roll 74 is chrome plated or the like to prevent corrosion by the high-temperature molten metal. The chill roll 74 can be rotated in the direction of the arrow at a predetermined rotation speed by a drive device (not shown).

[0052] To obtain a main phase having an average grain size of 1 to 10 μm, the cooling rate of the molten metal is, for example, 5° C. / sec or more, 10° C. / sec or more, or 10 2 °C / sec or more, and 3 ℃ / sec or less, 10 3 ℃ / sec or less, 5℃×10 2 In order to cool the molten metal at such a rate, the peripheral speed of the chill roll 74 may be 0.5 m / s or more, 1.0 m / s or more, or 1.5 m / s or more, and may be 3.0 m / s or less, 2.5 m / s or less, or 2.0 m / s or less.

[0053] The temperature of the molten metal when it is supplied from the end of the tundish 73 to the chill roll 74 may be 1350°C or more, 1400°C or more, or 1450°C or more, and may be 1600°C or less, 1550°C or less, or 1500°C or less.

[0054] The molten metal 72 is cooled and solidified on the outer circumference of the chill roll 74, becomes a magnetic alloy 75, is peeled off from the chill roll 74, and is recovered by a recovery device (not shown). The magnetic alloy 75 is typically in the form of a thin ribbon or flakes. The atmosphere in which the molten metal is cooled using the strip casting method is preferably an inert gas atmosphere to prevent oxidation of the molten metal, etc. The inert gas atmosphere includes a nitrogen gas atmosphere.

[0055] The ribbon or flake obtained as described above is pulverized to obtain a magnetic powder. The pulverization method is not particularly limited, but examples include a method in which the magnetic ribbon or flake is coarsely pulverized, and then further pulverized with a jet mill and / or a cutter mill. Examples of the coarse pulverization method include a method using a hammer mill, and a method in which the magnetic ribbon and / or flake is pulverized by hydrogen embrittlement. These methods may be combined.

[0056] The magnetic powder obtained as described above is sintered at 900 to 1100°C to obtain a sintered body. In order to increase the density of the sintered body by sintering without pressure, sintering is performed at high temperatures for a long time. The sintering temperature may be, for example, 900°C or more, 950°C or more, or 1000°C or more, and 1100°C or less, 1050°C or less, or 1040°C or less. By sintering at such a temperature, so-called liquid phase sintering is performed in which sintering progresses while a part of the magnetic powder is in a liquid phase. The sintering time may be, for example, 1 hour or more, 2 hours or more, 3 hours or more, or 4 hours or more, and may be 24 hours or less, 18 hours or less, 12 hours or less, or 6 hours or less. In order to suppress oxidation of the magnetic powder during sintering, the sintering atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere.

[0057] To improve the density of the sintered body, the magnetic powder may be pre-compacted before sintering, and the compacted body may be sintered. The molding pressure during powder compaction may be, for example, 50 MPa or more, 100 MPa or more, 200 MPa or more, or 300 MPa or more, and may be 1000 MPa or less, 800 MPa or less, or 600 MPa or less. To impart anisotropy to the sintered body, powder compaction may be performed while applying a magnetic field to the magnetic powder. The applied magnetic field may be 0.1 T or more, 0.5 T or more, 1.0 T or more, 1.5 T or more, or 2.0 T or more, and may be 10.0 T or less, 8.0 T or less, 6.0 T or less, or 4.0 T or less.

[0058] A modifier is diffused and infiltrated into the interior of the rare earth magnet precursor obtained by the method described so far. This will be described below.

[0059] 〈Modifier Diffusion and Infiltration Step〉 A modifier containing a rare earth element is diffused and infiltrated into the interior of the rare earth magnet precursor. This modifier contains La, and the molar ratio x of La to the total rare earth elements in the modifier satisfies 0.09 < x < 0.19. By setting the molar ratio x of La within the above range, the phase having the RT2-type crystal structure present in the grain boundary phase of the rare earth magnet precursor can be eliminated. As a result, a decrease in coercivity can be suppressed, and a decrease in squareness can be suppressed.

[0060] The melting points of rare earth elements are generally high. The modifier is typically composed of an alloy of a rare earth element and a transition metal element other than the rare earth element. Therefore, the melting point of such a modifier is lower than the melting point of the rare earth element. Therefore, typically, the modifier can be melted at a temperature lower than the melting point of the rare earth element, and the melt of the modifier can be diffused and infiltrated into the interior of the rare earth magnet precursor.

[0061] The content ratio of the transition metal elements other than the rare earth elements in the modifier may be appropriately determined so that the molten modifier can diffuse and penetrate into the rare earth magnet precursor. Except for lowering the melting point of the modifier, the transition metal elements other than the rare earth elements in the modifier hardly contribute to the elimination of the phase having the RT2 type crystal structure present in the grain boundary phase of the rare earth magnet precursor. Therefore, the elimination of the phase having the RT2 type crystal structure present in the grain boundary phase of the rare earth magnet precursor may be mainly considered with respect to the molar ratio x of La to the total rare earth elements in the modifier.

[0062] From the viewpoint of completely eliminating the phase having an RT2 type crystal structure present in the grain boundary phase of the rare earth magnet precursor, the molar ratio x of La may be greater than 0.09, 0.10 or more, 0.11 or more, or 0.12 or more. From the viewpoint of preventing the phase having an RT2 type crystal structure present in the grain boundary phase of the rare earth magnet precursor from being reformed, the molar ratio x of La may be less than 0.19, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, or 0.13 or less.

[0063] The composition of the modifier described above can be expressed by the following formula, for example:

[0064] The composition of the modifier is, for example, expressed by a molar ratio as follows: 2 (1-x) La x ) (1-s) M 2 s In this formula, R 2 and La is (1-s) moles, and M 2 means that it is s moles. Also, R 2 (1-x) La x ) is R 2 and La, in a molar ratio of (1-x) 2 This means that there exists an La of x.

[0065] In the above formula, R 2may be one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho. 2 is R 2 The rare earth elements may be metal elements other than rare earth elements that are alloyed with the rare earth elements, and unavoidable impurity elements.

[0066] The constituent elements of the modifier represented by the above formula will now be described.

[0067] ·R 2 R 2 is the main element of the modifier. As mentioned above, R 2 may be one or more elements selected from the group consisting of Nd, Pr, Gd, Tb, Dy, and Ho, which magnetically separates the main phases and improves the coercive force. 2 It is preferable that at least a part of R is a heavy rare earth element. 2 R is preferably one or more elements selected from the group consisting of Nd and Tb. 2 When Nd and Pr are used together, didymium may be used.

[0068] ·La As explained above, La contributes to the elimination of the phase having the RT2 type crystal structure present in the grain boundary phase of the rare earth magnet precursor. The content ratio of La is as explained above, and x in the above formula may be more than 0.09, 0.10 or more, 0.11 or more, or 0.12 or more, and may be less than 0.19, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, or 0.13 or less.

[0069] M 2 M 2 is R 2 Metal elements other than rare earth elements that are alloyed with unavoidable impurity elements, typically M 2 is R 2 (1-s) M 2 s The melting point of R 2These are alloying elements and unavoidable impurity elements that lower the melting point of M. 2 Examples of R include one or more elements selected from Cu, Al, Co, and Fe, as well as unavoidable impurity elements. 2 (1-s) M 2 s From the viewpoint of the melting point depression of M 2 As the oxide, Cu is preferable.

[0070] ·R 2 and M. 2 Molar ratio of R 2 and M. 2 is the molar ratio formula R 2 (1-s) M 2 s The alloy has a composition represented by the formula: s may be 0.05 to 0.40. When s is 0.05 or more, the modifier can be diffused and infiltrated into the rare earth magnet precursor at a temperature at which coarsening of the main phase can be avoided. From this viewpoint, s is preferably 0.10 or more, and more preferably 0.15 or more. On the other hand, when s is 0.40 or less, the M remaining in the grain boundary phase of the rare earth magnet after the modifier has been diffused and infiltrated into the rare earth magnet precursor can be reduced. 2 In this respect, s may be 0.35 or less, 0.30 or less, 0.25 or less, 0.20 or less, or 0.18 or less.

[0071] The method of preparing the modifier having the above-mentioned composition is not particularly limited, and a well-known method can be adopted. For example, a method of obtaining a thin strip and / or a thin piece from a molten metal having the composition of the modifier using a liquid quenching method or a strip casting method can be mentioned. In this method, since the molten metal is quenched, there is little segregation in the modifier, which is preferable. In addition, a method of preparing the modifier can be, for example, casting a molten metal having the composition of the modifier into a mold such as a book mold. In this method, a large amount of the modifier can be obtained relatively easily. In order to reduce the segregation of the modifier, it is preferable that the book mold is made of a material with high thermal conductivity. In addition, it is preferable to suppress the segregation by subjecting the cast material to a homogenizing heat treatment. In addition, a method of preparing the modifier can be mentioned in which the raw material of the modifier is charged into a container, the raw material is arc-melted in the container, and the molten material is cooled to obtain an ingot. In this method, even if the melting point of the raw material is high, the modifier can be obtained relatively easily. From the viewpoint of reducing segregation of the modifier, it is preferable to subject the ingot to a homogenizing heat treatment.

[0072] There is no particular limitation on the method for diffusing and penetrating the modifier into the rare earth magnet precursor, and any known method can be used. A typical example is to bring the modifier into contact with the rare earth magnet precursor to obtain a contact body, and then heat the contact body to cause the molten modifier to diffuse and penetrate into the rare earth magnet precursor.

[0073] The form of the contact body is not particularly limited as long as the rare earth magnet precursor is in contact with the modifier. Examples of the form of the contact body include a form in which the rare earth magnet precursor is in contact with a ribbon and / or flake of modifier obtained by a strip casting method, or a form in which the rare earth magnet precursor is in contact with modifier powder obtained by pulverizing a strip cast material, a book mold material, and / or an arc melted and solidified material.

[0074] The diffusion temperature is not particularly limited as long as the modifier diffuses into the rare earth magnet precursor and the main phase does not become coarse. Typically, the diffusion temperature is equal to or higher than the melting point of the modifier and equal to or lower than the sintering temperature at which the rare earth magnet precursor is obtained. The diffusion temperature may be, for example, 750°C or higher, 775°C or higher, or 800°C or higher, and may be 1000°C or lower, 950°C or lower, 925°C or lower, or 900°C or lower.

[0075] During the diffusion and penetration of the modifier, in order to suppress oxidation of the rare earth magnet precursor and / or the modifier, the diffusion and penetration atmosphere is preferably an inert gas atmosphere, including a nitrogen gas atmosphere.

[0076] The diffusion and penetration of the modifier may be combined with the heat treatment described later. In this case, the heating and cooling conditions of the modifier may be appropriately determined with reference to the conditions of the heat treatment. This allows the diffusion and penetration of the modifier to magnetically separate the main phases and align the interfaces between the main phases and the grain boundary phases, improving the magnetic properties, especially the coercive force.

[0077] In the manufacturing method of the present disclosure, a modifier containing a predetermined ratio of La is diffused and infiltrated into the rare earth magnet precursor, thereby eliminating the phase having the RT2 type crystal structure. The rare earth magnet precursor before the modifier is diffused and infiltrated has a very small coercive force, but the main phases are magnetically separated from each other by the diffusion and infiltration of the rare earth elements other than La in the modifier, and the coercive force is significantly improved. Therefore, the amount of the modifier diffused and infiltrated can be approximately the same as that of the conventional method. The amount of the modifier diffused and infiltrated can be, for example, 0.1 parts or more, 0.5 parts or more, 1.0 parts or more, 1.5 parts or more, 2.0 parts or more, 2.3 parts or more, 2.5 parts or more, 3.0 parts or more, or 10.0 parts or less, 9.0 parts or less, 8.0 parts or less, 7.0 parts or less, 6.0 parts or less, 5.0 parts or less, 4.0 parts or less, or 3.5 parts or less, relative to 100 parts of the rare earth magnet precursor, in molar ratio. In particular, the amount of the modifier diffused may be 2.0 parts or more, 2.3 parts or more, 2.5 parts or more, or 3.0 parts or more, and may be 6.0 parts or less, 5.5 parts or less, or 5.0 parts or less.

[0078] <Heat treatment process> When the grain size of the main phase is 1 to 10 μm, the rare earth magnet precursor may be optionally heat-treated before and / or after the diffusion and penetration of the modifier to align the interface between the main phase and the grain boundary phase and improve the magnetic properties, particularly the coercive force. In order to suppress oxidation of the rare earth magnet precursor during the heat treatment, the heat treatment atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere. As such a heat treatment, the rare earth magnet precursor may be heat-treated at 450 to 650°C for 30 to 180 minutes, preferably at 500 to 600°C for 45 to 90 minutes.

[0079] 《Transform》 In addition to what has been described so far, the manufacturing method of the present disclosure can be modified in various ways within the scope of the contents described in the claims. In the above description, the rare earth magnet precursor is a sintered body, but this is not limited to this, and for example, a so-called two-alloy method can be adopted. Specifically, a powdered rare earth magnet precursor is prepared, mixed with a modifier powder, and sintered. The sintering temperature and sintering time can be appropriately determined so as to achieve both pressureless sintering and diffusion and penetration of the modifier. The sintering temperature may be, for example, 900°C or higher, 950°C or higher, or 1000°C or higher, and 1100°C or lower, 1050°C or lower, or 1040°C or lower. The sintering time may be, for example, 1 hour or more, 2 hours or more, 3 hours or more, or 4 hours or more, and 24 hours or less, 18 hours or less, 12 hours or less, or 6 hours or less. In order to suppress oxidation of the rare earth magnet precursor and the modifier during sintering, the sintering atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere. EXAMPLES

[0080] The manufacturing method of the present disclosure will be described in more detail below with reference to examples and comparative examples. Note that the manufacturing method of the present disclosure is not limited to the conditions used in the following examples.

[0081] <Sample preparation> Samples of Example 1 and Comparative Examples 1 to 8 were prepared according to the following procedure.

[0082] A strip cast material (magnetic ribbon) having the composition shown in Table 1-1 and Table 1-2 was prepared. The strip cast material was coarsely crushed by hydrogen embrittlement, and then further crushed using a jet mill to obtain a magnetic powder. The magnetic powder was pressureless sintered (pressureless liquid phase sintering) at 1050°C for 4 hours. After sintering, the sintered body was cooled to room temperature to obtain a rare earth magnet precursor. The modifier ribbon was brought into contact with the rare earth magnet precursor to obtain a contact body. The contact body was heated at 950°C for 165 minutes to diffuse and infiltrate the modifier into the rare earth magnet precursor. The rare earth magnet precursor after diffusion and infiltration was then cooled to room temperature at a rate of 1.0°C / min, and then heat-treated at 550°C for 60 minutes to obtain each sample. However, the heat treatment temperature for the sample of Comparative Example 8 was set to 500°C.

[0083] "evaluation" The magnetic properties of each sample were measured at 27° C. using a vibrating sample magnetometer (VSM).

[0084] Each sample was observed using a scanning electron microscope (SEM) to determine the average grain size of the main phase. In addition, surface analysis was performed for Fe, Co, Nd, Tb, and La using a scanning electron microscope-energy dispersive X-ray spectroscope (SEM-EDX).

[0085] The results are shown in Tables 1-1 and 1-2 and Figures 6 to 10. Figure 6 is a graph showing the relationship between the molar ratio x of La to the total rare earth elements in the modifier and the squareness ratio (Hr / Hc) for each sample. Figure 7 is a graph showing the demagnetization curves for each sample. Figure 8 is an explanatory diagram showing SEM images and area analysis results for the sample of Example 1. Figure 9 is an explanatory diagram showing SEM images and area analysis results for the sample of Comparative Example 1. Figure 10 is an explanatory diagram showing SEM images and area analysis results for the sample of Comparative Example 5. In the area analysis results of Figures 8 to 10, the areas where the concentration of the relevant element is high are bright fields.

[0086]

Table 1-1

[0087]

Table 1-2

[0088] As can be seen from Table 1 and FIGS. 6 to 7, it can be understood that when 0.09 < x < 0.19, the decrease in squareness is suppressed. Further, in FIGS. 8 to 10, the site where the surface analysis result of Fe is a dark field and the surface analysis result of Co is a bright field is the site where the phase having the RT2-type crystal structure exists. Such a site is only slightly recognized in the sample of Example 1. On the other hand, in the sample of Comparative Example 1 in which a modifier substantially free of La was diffusion-infiltrated, many such sites are recognized in the adjacent portions and the like. Further, in the sample of Comparative Example 5 in which a modifier containing an excessive amount of La was diffusion-infiltrated, many such sites are recognized at the triple points, and it is considered that the phase having the RT2-type crystal structure is reformed. Further, it is recognized that excessive La exists in the adjacent portions.

[0089] From the above results, the effect of the manufacturing method of the present disclosure could be confirmed.

Explanation of Signs

[0090] 10 Matrix phase 20 Grain boundary phase 22 Adjacent portion 24 Triple point 26 Phase having RT2-type crystal structure 28 La phase 50 Rare earth magnet precursor 70 Cooling device 71 Melting furnace 72 Molten metal 73 Tundish 74 Cooling roll 75 Magnetic alloy 100 Rare earth magnet

Claims

1. R 2 T 14 preparing a rare earth magnet precursor comprising a main phase having a B-type crystal structure (where R is a rare earth element and T is a transition metal element) and a grain boundary phase present around the main phase; Diffusing and penetrating a modifier containing a rare earth element into the rare earth magnet precursor; Including, The rare earth magnet precursor has an overall composition in terms of molar ratio represented by the formula R 1 y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v , where R 1 is one or more elements selected from the group consisting of Nd and Pr, M 1 is one or more elements selected from the group consisting of Ga, Al, and Cu, and unavoidable impurity elements, 12.0≦y≦20.0, 0.10≦z≦0.30, 5.0≦w≦20.0, and 0≦v≦2.0 ) is expressed as The average grain size of the main phase is 1 to 10 μm, The composition of the modifier is represented by the formula (R 2 (1-x) La x (1-s) M 2 s (wherein R 2 is one or more elements selected from the group consisting of Nd and Tb, M 2 is Cu and an unavoidable impurity element, and 0.09<x<0.19 and 0.05≦s≦0.40) in molar ratio. A method for manufacturing rare earth magnets.

2. y is 13.5 or more and 13.9 or less, w is equal to or greater than 5.7 and equal to or less than 5.8; v is equal to or greater than 0.2 and equal to or less than 0.5; x is equal to or greater than 0.12 and equal to or less than 0.13; s is 0.15 or more and 0.20 or less; The method for producing the rare earth magnet according to claim 1.

Citation Information

Patent Citations

  • R-t-b-based permanent magnet

    JP2014216463A

  • Method for manufacturing rare earth magnet

    JP2019140279A

  • Method for manufacturing r-t-b based sintered magnet

    JP2020155657A